Drawing Careers: The Value of a Biographical Mapping Method in Qualitative Health Research. Issue 1 (19th February 2019) - Schubring, Astrid; Mayer, Jochen; Thiel, Ansgar
Narrative interviews are the methodological gold standard for biographical research. To facilitate memory work in interviewees, qualitative researchers increasingly fuse interviewing with visual elicitation strategies. In this article, we advance the integration of methods by introducing a graphic elicitation strategy that allows interviewees to map biographical developments and critical health experiences, in addition to verbalizing them. The biographical mapping approach was originally developed for a research project on adolescents' health and illness experiences in elite sport but lends itself to qualitative biographical research in general. Using case material, we first demonstrate how the mapping process helps interviewees to recall past episodes and to produce more detailed biographical data. Second, we describe how the depth of focus in the biographical drawing and interview data allows researchers to identify biographical turning points and to analyze interactions between context, life events, and health in a unique way. By visualizing different strands of development, the elicited drawings also hold heuristic value, as they show the nonlinearity and multidimensionality of biographical developments.